2020
DOI: 10.1002/acn3.51168
|View full text |Cite
|
Sign up to set email alerts
|

Altered coupling between resting‐state glucose metabolism and functional activity in epilepsy

Abstract: Objective: Altered functional activities and hypometabolism have been found in medial temporal lobe epilepsy patients with hippocampal sclerosis (mTLE-HS). Hybrid PET/MR scanners provide opportunities to explore the relationship between resting-state energy consumption and functional activities, but whether repeated seizures disturb the bioenergetic coupling and its relationship with seizure outcomes remain unknown. Methods: 18 F-FDG PET and restingstate functional MRI (rs-fMRI) scans were performed with hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Nevertheless, hypermetabolism in focal brain regions/networks is not necessarily associated with an elevated FC and a higher conscious level. For example, although a coupling between the energy consumption and neural activity within a gray matter is reported in epileptic status; however, this metabolic synchronization is spatially heterogeneous throughout the brain, in the regions showing hypermetabolism and an increased FC, generation and propagation of epileptiform activity usually occur; in contrast, in the regions partly located in the areas corresponding to the DMN, showing hypometabolism and an decreased functional activity, information communication is interrupted (Wang et al, 2020 ), suggesting that widespread, asymmetric, and often severe interictal metabolic alterations play a critical role in epileptic loss of consciousness. In other words, a neurometabolic decoupling in neuroglial populations might play a role in a higher coupling, which may be the modulating result linked to the strong hyperexcitability generated by epileptiform activity.…”
Section: Brain Metabolism Neural Activity and Consciousnessmentioning
confidence: 99%
“…Nevertheless, hypermetabolism in focal brain regions/networks is not necessarily associated with an elevated FC and a higher conscious level. For example, although a coupling between the energy consumption and neural activity within a gray matter is reported in epileptic status; however, this metabolic synchronization is spatially heterogeneous throughout the brain, in the regions showing hypermetabolism and an increased FC, generation and propagation of epileptiform activity usually occur; in contrast, in the regions partly located in the areas corresponding to the DMN, showing hypometabolism and an decreased functional activity, information communication is interrupted (Wang et al, 2020 ), suggesting that widespread, asymmetric, and often severe interictal metabolic alterations play a critical role in epileptic loss of consciousness. In other words, a neurometabolic decoupling in neuroglial populations might play a role in a higher coupling, which may be the modulating result linked to the strong hyperexcitability generated by epileptiform activity.…”
Section: Brain Metabolism Neural Activity and Consciousnessmentioning
confidence: 99%
“…Standard uptake value ratio (SUVr) maps were converted by dividing the mean value of reference region. According to previous research [30,31], cerebellum gray matter was chosen as the reference region. With regard to high-resolution PET data acquisition, there was less need to perform partial volume effect correction.…”
Section: Metabolic Connectivity Map (Mcm) Analysismentioning
confidence: 99%
“…9 Zeng et al used ReHo analysis to confirm abnormal regional synchronization in specific brain regions of patients with mesial TLE. 10 Cheng et al observed increased ReHo values in the hippocampus, thalamus, and parietal lobes but decreased ReHo values in the posterior cerebellum lobe in TLE patients. 11 All these published mass univariate studies investigating ReHo alterations between TLE patients and normal controls (NC) aim to test whether some brain regions have any difference, rather than to test whether these differences can be used to distinguish TLE patients and NC.…”
Section: Introductionmentioning
confidence: 98%